Hatthavanagallavihāra vaṃśaya - Dhammaratana, Uturāvala, Himi. ([Kǎḷaniya] : Uturāvala Dhammaratana, 1982)
Thirteenth century Pali (Sinhalese script) verse work on Saṅghabōdhi (Sirisaṅgabō), 3rd century king of Sri Lanka.
In Pali (Sinhalese script); translation in Sinhalese.
Mode of access: Internet.
Keywords: Sirisaṅgabō, -- King of Ceylon, -- 3rd cent. B.C. -- Poetry